ANALISIS SALURAN DAN TINGKAT EFISIENSI PEMASARAN BERAS SEMI ORGANIK DI KECAMATAN KOTA AGUNG KABUPATEN LAHAT - Iskandar marlian (Jurnal Ilmu Pertanian Kelingi, 2022)
Semi-organic rice is an environtmentally and consumer friendly food product. However, one of the main problem associated with semi-organic rice and organic food in general is marketing, since it has spesific consumer and relatively higher price. Thus, studies focused on semi-organic marketing is of paramount important. The objectives of this study are, to identify marketing channel for semi-organic rice from farmer to consumer, analyze structure and conduct of semi-organic rice market, and analyze marketing efficiency of each marketing channel and the efficiency of each marketing organization in each channel. This study employed survey method based on questionnaire to guide the interview. The sample used in this study are 30 farmers randomly selected from a population of 95 semi-organic rice farmers located at Pagaruyung village, on Kota Agung sub-district, in the district of Lahat. Based on 30 sample farmers, the marketing channel for semi-organic rice was traced using snowball method and 2 collecting trader and 1 retail trader were identified. The result shows that there are two channels in the marketing of semi organic rice in the studied area, channel 1 (farmer-village level collecting trader-large collecting trader-retail trader-consumer) and channel 2 (farmer-village level collecting trader-konsumer). The second result shows that semi-organic rice market in the studied area tend to be monopolistic since there is no single actor control consumer, price, product, and transaction. The final result shows that each marketing channel of semi-organic rice is efficient.